2022
DOI: 10.1101/2022.11.03.514990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liver type 1 innate lymphoid cells lacking IL-7 receptor are a native killer cell subset fostered by parenchymal niches

Abstract: Group 1 innate lymphoid cells (G1-ILCs), including circulating natural killer (NK) cells and tissue-resident type 1 ILCs (ILC1s), are innate immune sentinels critical for responses against infection and cancer. In contrast to relatively uniform NK cells through the body, diverse ILC1 subsets have been characterized across and within tissues in mice, but their developmental and functional heterogeneity remain unsolved. Here, using multimodalin vivoapproaches including fate-mapping and targeting of the interleuk… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…This concept holds true for the LTi cell and ILC3 38,46,58,59 lineages 32 (Figure 2). Studies have shown that also ILC1 4,88–90 and ILC2 91 have an embryonic wave, seeding embryonic tissues such as fetal liver, LN anlagen, gut and lung and being gradually replaced during life by cells derived from bone‐marrow residing progenitors. To better identify the descendants of these specific waves, precise fate‐mapping models are required.…”
Section: Discussionmentioning
confidence: 99%
“…This concept holds true for the LTi cell and ILC3 38,46,58,59 lineages 32 (Figure 2). Studies have shown that also ILC1 4,88–90 and ILC2 91 have an embryonic wave, seeding embryonic tissues such as fetal liver, LN anlagen, gut and lung and being gradually replaced during life by cells derived from bone‐marrow residing progenitors. To better identify the descendants of these specific waves, precise fate‐mapping models are required.…”
Section: Discussionmentioning
confidence: 99%
“…24,53,54 Despite differential IL7R expression, ILC1s are independent of IL7 and are not diminished in IL7 knockout mice. 24 Functionally, liver ILC1s play an important role, in a nonredundant manner, to control cancer metastases to liver and also provide protection against acute liver injury. 56,57 Three clusters of liver NK cells were observed in a recent scRNAseq analysis.…”
Section: Liver Group 1 Ilcsmentioning
confidence: 98%
“…Several transcriptomic and proteomic studies have identified multiple transcription factors, including Nfil3, ID2, TOX, TCF1, and PLZF1 that orchestrate ILC development downstream of CLPs. 16,[18][19][20][21][22][23][24][25][26] The earliest common progenitors that differentiate from CLPs and can give rise to all three groups of ILCs are termed early innate lymphoid progenitors (EILPs).…”
Section: Ilc De Velopmentmentioning
confidence: 99%
See 2 more Smart Citations